A critical examination of the phenomenon of post-truth - Cabaneros, Jaybee S. (Animo Repository, 2021)
In the contemporary era, the truth is generally being doubted. Various philosophers say that it is the result of postmodernism to which a new term—the Post-Truth— was created to describe this phenomenon. The term ‘post-truth’ became well-known after the Oxford Dictionary chose it as the “Word of the Year” in 2016. It serves as a term that perfectly describes and represents the occurrences in the contemporary era. This is a new phenomenon created from the information explosion by the modern media that sets out to confuse people between what is true and what is a lie.Many references of this phenomenon point to the events in 2016 when Trump won the US presidency. This led various thinkers to write about the disappearance of the shared objective in philosophical and political discourses. These discourses helped this paper in establishing and identifying the parallel events that are happening in the Philippines. The paper examined Duterte politics as a concrete example of the phenomenon of post-truth. The term was born from a sense of regret by those who worry that truth is being eclipsed. For some aspects, at least, the term presumes a point of view: that facts and truth are endangered in today’s political arena (Mclntyre, 2020). Thus, this research analyzed the origin, occurrence, and impact of the post-truth phenomenon. This paper is a critical examination as it identifies a new philosophical problem that affects the authority of truth. The post-truth phenomenon undermines, subverts, and devalues the truth. This paper discussed its elements to understand the phenomenon.This thesis cites various philosophers, including Hannah Arendt and George Orwell who are pointed as the harbingers of the phenomenon. It also discusses Jacques Derrida’s deconstruction, Michel Foucault’s regime of truth, and other contemporary philosophers. The paper basically argues that post-truth exists within our time. But, how it occurs in our time, particularly in the Philippines, is yet to be known.